2sin (pi-a) cos (pi / 2-a) + 3sin ^ 2 (pi / 2-a) -2.

2sin (pi-a) cos (pi / 2-a) + 3sin ^ 2 (pi / 2-a) -2.

  •  2sin (\ pi - \ alpha) * cos (\ frac {\ pi} {2} - \ alpha) +3 sin ^ {2} (\ frac {\ pi} {2} - \ alpha) -2 =
    = 2sin \ alpha * sin \ alpha +3 (sin (\ frac {\ pi} {2} - \ alpha)) ^ {2} -2 = 2 sin ^ {2} \ alpha + 3cos ^ {2} \ alpha -2 =
     (2 sin ^ {2} \ alpha +2 cos ^ {2} \ alpha) + cos ^ {2} \ alpha - 2 = 2 * (sin ^ {2} \ alpha + cos ^ {2} \ alpha) + cos ^ {2} \ alpha -2 =
    = 2 * 1 + cos ^ {2} \ alpha -2 = cos ^ {2} \ alpha

You may also like

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *

7 + 3 =